Respostas
respondido por:
0
( x + 1 )² + ( x - 1 ) ² = 0
( x² + 2x + 1 ) + ( x² - 2x + 1 ) = 0
x² + 2x + 1 + x ² - 2x + 1 = 0
2x² + 2 = 0
2x² = -2
x² = -(2/2)
x² = -1
x = ±√-1 = ±į
x = ±į
( x² + 2x + 1 ) + ( x² - 2x + 1 ) = 0
x² + 2x + 1 + x ² - 2x + 1 = 0
2x² + 2 = 0
2x² = -2
x² = -(2/2)
x² = -1
x = ±√-1 = ±į
x = ±į
Negadasilva:
Me ajudou muito so não entendi o penúltimo e o último
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás